Principles of glycocalyx engineering with hydrophobic-anchored synthetic mucins - Wardzala, Casia L.; Clauss, Zachary S.; Kramer, Jessica R. (Frontiers in Cell and Developmental Biology, 2022)
The cellular glycocalyx is involved in diverse biological phenomena in health and disease. Yet, molecular level studies have been challenged by a lack of tools to precisely manipulate this heterogeneous structure. Engineering of the cell surface using insertion of hydrophobic-terminal materials has emerged as a simple and efficient method with great promise for glycocalyx studies. However, there is a dearth of information about how the structure of the material affects membrane insertion efficiency and resulting density, the residence time of the material, or what types of cells can be utilized. Here, we examine a panel of synthetic mucin structures terminated in highly efficient cholesterylamide membrane anchors for their ability to engineer the glycocalyx of five different cell lines. We examined surface density, residence time and half-life, cytotoxicity, and the ability be passed to daughter cells. We report that this method is robust for a variety of polymeric structures, long-lasting, and well-tolerated by a variety of cell lines.